Study on the Characteristic Codon Usage Pattern in Porcine Epidemic Diarrhea Virus Genomes and Its Host Adaptation Phenotype - Si, Fusheng; Jiang, Li; Yu, Ruisong; Wei, Wenqiang; Li, Zhen (Frontiers in Microbiology, 2021)
Porcine epidemic diarrhea virus (PEDV), which classified in the genus Alphacoronavirus, family Coronaviridae, is one of the most important pathogens that cause heavy economic losses in pig industry. Although intensive mutation and recombination analysis of PEDV strains were provided, systematic genome analysis were needed to elucidate the evolution mechanism and codon usage adaptation profiles of the pathogen. Here, a comprehensive investigation was carried out to reveal the systematic evolutionary processes of synonymous codon usage and host-adapted evolution phenotype of PEDV genome. We found a low codon usage bias (CUB) in PEDV genome and that nucleotide compositions, natural selection, mutation pressure and geographical diversity shapes the codon usage patterns of PEDV, with natural selection dominated the overall codon usage bias in PEDV than the others. By using the relative codon deoptimization index (RCDI) and similarity index (SiD) analysis, we observed that genotype II PEDV strains showed the highest level of adaptation phenotype to Sus scrofa than another divergent clade. To the best of our knowledge, this is the first comprehensive report elaborating the codon usage and host adaptation of PEDV. The findings offer an insight into our understanding of factors involved in PEDV evolution, adaptation and fitness towards their hosts.